Strategi Pencegahan Stunting Berbasis Pendekatan Kesehatan Masyarakat Di Kota Makassar: Analisis Intervensi Multisektoral - Jusman Usman; Anrina Ariyanti (Jurnal Anestesi, 2026)
The urgency of this research lies in the high prevalence of stunting in Makassar City, which reflects systemic public health challenges. Stunting has long-term impacts on the quality of human resources, economic productivity, and national resilience. Objective: The primary objective of this study is to evaluate the effectiveness of multisectoral interventions in stunting prevention efforts from a public health perspective. Method: This study employs a qualitative method with a case study approach, utilizing data collection techniques that include in-depth interviews, observations, and document reviews. The analysis was conducted thematically with NVivo 12 Plus to identify intervention patterns, key actors, and supporting and inhibiting factors in stunting prevention efforts. Results: The study's results indicate that stunting prevention in Makassar City is effective when implemented through a public health approach that integrates specific and sensitive nutrition interventions in a multisectoral manner, involving health workers, communities, government agencies, and the private sector. Specific nutrition interventions such as nutrition education, supplementary feeding, and toddler growth monitoring improve family knowledge, although program coverage and sustainability remain limited. While nutrition-sensitive interventions, such as providing clean water and adequate sanitation, reduce the risk of stunting, they are hindered by uneven infrastructure. The role of health workers, midwives, and integrated health posts (Posyandu) cadres is crucial. However, their capacity needs to be strengthened, and community participation is uneven due to social, economic, and cultural factors. Other obstacles include limited access to services, delays in nutrition monitoring, and suboptimal cross-sectoral coordination. These findings underscore the importance of a multisectoral, public health-based strategy that prioritizes human resource strengthening, utilizes real-time spatial data, fosters regular coordination forums, and empowers communities to ensure interventions are targeted, effective, and sustainable. Conclusion: Stunting prevention in Makassar City is effective when implemented through an integrated, multisectoral, public health-based strategy supported by human resource strengthening, real-time spatial data, regular coordination, and active community participation. Recommendation: The government and stakeholders must strengthen cross-sectoral coordination, health worker capacity, and community empowerment to sustainably increase the effectiveness of stunting prevention interventions